A new route to graphene starting from heavily ozonized fullerenes: Part 1—thermal reduction under inert atmosphere. Issue 1 (2nd January 2016) - Cataldo, Franco; Putz, Mihai V.; Ursini, Ornella; Angelini, Giancarlo; Garcia-Hernandez, D. Anibal; Manchado, Arturo
Abstract : It is shown that heavily ozonized C60 or C70 fullerenes (known also as "fullerene ozopolymers") are suitable substrates for the preparation of graphene or nanographene in place of graphite oxide (GO) by thermal reduction in inert atmosphere. TGA-FTIR study shows that the release profile of CO2 and CO from fullerene ozopolymers in the temperature range between 25°C and 900°C is comparable to that shown by GO. Furthermore, the FT-IR spectral evolution of fullerene ozopolymers from room temperature to 630°C under inert atmosphere is once again strikingly comparable to that observed on GO under the same conditions.